Hubungan Pendarahan Bercak Ringan (Spoting), Peningkatan Berat Badan dan Perubahan Siklus Haid Dengan Pemakaian Kontrasepsi Implan Pada Akseptor KB di Puskesmas Pegayut Kabupaten Ogan Ilir - Magumi, Novita; Qur’andini, Dalinur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Several factors influence the use of contraceptive implants, including light spotting, weight gain, changes in menstrual cycles, and nausea and vomiting. This study used an analytical survey method with a cross-sectional design. The population was all mothers who were accepting family planning who visited the Pegayut Community Health Center in Ogan Ilir Regency. the Chi-Square statistical test, a p value of 0.000 was obtained (? = ? 0.05), meaning that there is a significant relationship between light spotting and the use of implant contraception at the Pegayut Health Center, Ogan Ilir Regency, and the results of the Chi-Square statistical test, a p value of 0.002 was obtained (? = ? 0.05), meaning that there is a significant relationship between weight gain and the use of implant contraception at the Pegayut Health Center, Ogan Ilir Regency. Thus, the hypothesis that states there is a relationship between weight gain and the use of implant contraception is statistically proven. Thus, there is a relationship between Light Spotting, Weight Gain and changes in the menstrual cycle with the use of Implant contraception at the Pegayut Health Center, Ogan Ilir Regency. It is hoped that health workers will improve health services and counseling among mothers, especially health workers (midwives) and policy makers in the implementation of health services so that acceptor mothers can gain knowledge about appropriate contraceptives.